What Kind of Medical Specialist Can Support Primary Health Transformation in Indonesia? - Dhanasari Vidiawati (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2023)
The transformation of basic health services that was proclaimed as part of the transformation of health services by the Minister of Health of the Republic of Indonesia in 2022 is a dream come true for me. Even though the World Health Organization (WHO) has been advocating for it since 2008 in its report Primary Care Now More Than Ever, Indonesia finally made it happen when the Ministry of Health was not led by a doctor. The emphasis on 'not working as a doctor' as the leader of the Ministry of Health seems to be 'beneficial' for primary health services in Indonesia, which so far has been under the shadow of the 'non-specialist and specialist' bureaucratic level of management which is equated with 'primary services and non-primary services'. So far, the terms and understanding of the government, BPJS, and doctors regarding medical specialist are essentially referral services, not primary services. It is as if a doctor working in primary care is considered not an expert. But if they become an expert, then they should be transferred to another place of work.